STUDENTS’ MASTERY OF SEMANTIC FIELD (A SEMANTIC RESEARCH AT NONENGLISH DEPARTMENT) - Kharisma Puspita Sari (Vision: Journal for Language and Foreign Language Learning, 2015)
This study aimed at investigating categories of semantic fi eldby nonenglish department students. The researcher designed thisresearch as explanatory qualitative research.There are three steps in holding this research. The fi rst stepis to collect the data. The data card is considered as the appropri-ate data. The nonenglish students’ aspirations of semantic fi eld arethe only data. The next step is to analyze the data. The researcherused the Riemer’s theory (the semantics of categorization) to ana-lyze the data. The students’aspiration would be classifi ed accordingto Riemer’s theory. The last step is to present the analysis. The re-searcher classifi ed the data into two categories: a) classical categori-zation, and b) prototype categorization. The dominant classical cat-egorization could be fi nd in the lexical items like house, bathroom,tree, concert, holiday, library, hospital, football competition,and aircraft. The researcher investigated dominant prototype cat-egorization in the lexical items as follows; car, ship, mountain,post offi ce, and minimarket.